The study of liophilization parameters in the liposomal irinotecan development - Stadnichenko, O. V.; Krasnopolsky, Yu. M.; Yarnykh, T. G. (Національний фармацевтичний університет, 2017)
The creation of the liposomal irinotecan is one of the main ways to reduce toxicity and increase the effectiveness of chemotherapy. Lyophilization makes it possible to obtain a product with a guaranteed stability of the size and encapsulation efficiency. Aim. To optimize the content of the cryoprotector in the liposomal irinotecan, and develop lyophilization parameters to produce liposomes with the maximum encapsulation of irinotecan in them, alongside while maintaining the nanosize. Materials and methods. Egg phosphatidylcholine from Lipoid (Germany) was used for preparation of liposomes. Lyophilization was carried out in a Quarco device (PR China). The encapsulation degree was determined on a Shimadzu LC-20 instrument (Japan) by HPLC method developed earlier. Results and discussion. The optimal content of the cryoprotector – trehalose dihydrate has been studied. It has been found that the optimal content of trehalose dihydrate is 8 % (w/w). The modes of the product lyophilization have been studied. The secondary drying temperature in the range of 10-20 °C has been determined. At the secondary drying temperature of 10 °C the residual moisture content was 5-8 %, which was beyond the target range. At 20 °C the water content in the lyophilizate was 0.5-0.8 %, the loss of encapsulation was up to 20 %. The mode of drying at 15 °C was optimal, while the residual water content in the lyophilizate was 1.5-2.8 %, the loss of encapsulation was 13 %, the size of the liposomes after lyophilization and rehydration did not change significantly compared to the initial one. Сonclusions. As a result of the studies, liposomes with irinotecan have been obtained. The content of trehalose dihydrate as a cryoprotector in the range of 4-10 % has been studied. It has been shown that the optimum content of trehalose dihydrate is 8 % (w/w); moreover, the encapsulation decrease in lyophilization is 13 %. The modes of the liposomal irinotecan lyophilization have been studied at the final drying temperature of 10, 15 and 20 °C. It has been found that the optimum final drying temperature is 15 °C.

Створення ліпосомальной форми іринотекану – один з основних шляхів зменшення токсичності і підвищення ефективності при проведенні хіміотерапії. Ліофілізація дозволяє отримувати продукт з гарантованим збереженням розмірів і параметрів інкапсуляції, тому дослідження параметрів даного процесу є актуальним. Метою дослідження є оптимізація вмісту кріопротектора в ліпосомальній формі іринотекану, розробка процесу ліофілізаціі для отримання ЛЗ з максимальною інкапсуляцією в них іринотекану при збереженні нанорозмірів. Матеріали та методи. Для виготовлення лікарського засобу використовували яєчний фосфатидилхолін фірми Lipoid, ліофілізацію проводили в апараті Quarco виробництва КНР. Визначення ступеня інкапсуляції проводили методом ВЕРХ на приладі Shimadzu LC 20. Результати та їх обговорення. Проведено дослідження вмісту кріопротектора – трегалози дигідрату. Встановлено, що оптимальним є вміст трегалози дигідрату 8 % (мас). Проведено вивчення режимів ліофілізації продукту. Вивчено температуру вторинного висушування від 10 до 20 °С. При температурі вторинного висушування 10 °С вміст залишкової вологи становив 5-8 %, що виходило за цільові рамки. При 20 °С вміст води в ліофілізаті становив 0,5- 0,8 %, втрата інкапсуляції – до 20 %. Оптимальним був режим при досушуванні при 15 °С, при цьому вміст залишкової води в ліофілізаті склав 1,5-2,8 %, втрата інкапсуляції склала 13 %, розмір ліпосом після ліофілізації та регідратації істотно не змінювався в порівнянні з вихідним значенням. Висновки. В результаті проведених досліджень отримані лікарські засоби з іринотеканом. Досліджено вміст трегалози дигідрату як кріопротектора в діапазоні від 4 до 10 %. Показано, що оптимальним є вміст трегалози дигідрату 8 % (мас), при цьому зниження інкапсуляції при ліофілізації становить 13 %. Досліджені режими ліофілізації лікарських засобів з іринотеканом при температурі досушування 10, 15, 20 °С. Встановлено, що оптимальною є температура досушування 15 °С.
Дослідження параметрів ліофілізації при одержанні ліпосомальної форми іринотекану
Keywords: liposomes; chemical gradient; high pressure extrusion; cryoprotector; freeze drying; ліпосоми; градієнт хімічний; екструзія; кріопротектор; сушка ліофільна